The Possible Role of Contact Sensitization to Fragrances and Preservatives in Poikiloderma of Civatte - Khunkhet, Saranya (Case Rep Dermatol, 2014)
Numerous mechanisms have been postulated to play an important role in the pathogenesis of poikiloderma of Civatte (PC), including chronic exposure to ultraviolet radiation, menopause-related hormonal changes, contact hypersensitivity and genetic predisposition. Herein, we report a case of contact sensitization to fragrances and commonly used preservatives, methylchloroisothiazolinone and methylisothiazolinone, also widely known as Kathon CG, in a post-menopausal woman with PC, who denied excessive sun exposure and a family history. After abstaining from the use of her personal care products containing the documented allergens, not only the itching and burning symptoms, but also the cutaneous changes appeared to improve partially. This report underlines the possible influence of contact hypersensitivity in the pathogenesis of PC.